The relationship between physical training, mental health, and nutrition on the performance of soccer athletes - Jori Lahinda; Isyani Isyani; Andi Gilang Permadi; Ainur Rasyid (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction and Objective. This study used a quantitative approach with the support of two computer programs, namely, VOSviewer and SmartPLS 4, to analyze the relationship between physical training and mental health of football players" and "nutrition for the performance of football players". From the Scopus database, this study collected 21 documents for the first keyword and 58 documents for the second.